A New Alternative Thinner in the Drilling Fluid System - AL-Hashimi, Wissam H. (Journal of Petroleum Research and Studies, 2018)
The most important constituent of drilling operation success is keeping the drilling fluid rheological properties within a certain limit to maintain continuing their functions in a good manner. To achieve that, the drilling mud system needs continuous and direct supervision such as measuring its rheological properties and treating any deviation in their values. Viscosity is the most important property in hydraulic program success due to its direct relation with bottom hole cleaning during drilling, thus related with the drilling rate, so this property should be kept basically to ensure bottom hole cleaning and high drilling rate at the same time. Some chemicals such as thinner should be added to the mud system to keep both viscosity and other properties within certain standards and required limits; these materials have a high cost, increasing both the metric cost and the final cost of such well. The aim of this research is to test the physical and chemical properties for a local material, as a thinner, which tends to decrease the rheological properties of drilling mud .Thirty nine samples of different types of drilling mud are tested with both the native and foreign imported materials. The results for both additive materials are compared and concluded that the local thinner has the same trend with the imported material to a certain limit.